Symptoms and cholinesterase activity among rural residents living near cotton fields in Nicaragua. Issue 11 (November 1996) - Keifer, M; Rivas, F; Moon, J D; Checkoway, H
Abstract : OBJECTIVES: To explore whether symptoms resulted from pesticide spray drift on residentially exposed populations in rural Nicaragua. METHODS: 100 residents, each 10 years of age or older, were randomly selected from a Nicaraguan community surrounded by actively sprayed cotton fields (the exposed community) and from a socioeconomically similar community far from agricultural spraying (the control community). Subjects working with pesticides were excluded, and the study was conducted at the end of the 1990 cotton spraying season (August-December). Demographic information, exposure questions, and prevalence of 11 acute symptoms and 17 chronic symptoms were gathered from a structured interview. Finger stick erythrocyte cholinesterase (AChE) was measured with a portable colorimeter. Acute symptoms were grouped according to their previously known associations with cholinesterase (ChE) inhibitors into four ordinal categories (asymptomatic, non-specific, possible, probable). RESULTS: Residents from the exposed community were significantly more likely to report recently sighting a spray plane near their community, exposure to pesticide from drift, crossing recently sprayed fields, eating home grown food, and feeling ill after drift exposure. The mean AChE value was significantly lower for residents of the exposed community (4.9 v 5.3 IU/dl). The proportion of subjects complaining of one or more chronic or acute symptoms was significantly higher for the exposed community (87%) than for the controls (53%). Odds ratios for residents in the exposed community, by symptom categories, were non-specific 1.6 (95% confidence interval (95% CI) 0-8 to 3.2), possible 4.1 (95% CI 1.7 to 10.2), and probable 9.93 (95% CI 2-9 to 34.4). CONCLUSION: These findings indicate a strong association between exposure to aerial pesticides and symptoms. This study should be replicated with more quantitative exposure measures, for if confirmed, the results have relevance for millions in rural communities worldwide.